If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(5y + 4) + -17 = 6(3y + -3) + -7 Reorder the terms: 5(4 + 5y) + -17 = 6(3y + -3) + -7 (4 * 5 + 5y * 5) + -17 = 6(3y + -3) + -7 (20 + 25y) + -17 = 6(3y + -3) + -7 Reorder the terms: 20 + -17 + 25y = 6(3y + -3) + -7 Combine like terms: 20 + -17 = 3 3 + 25y = 6(3y + -3) + -7 Reorder the terms: 3 + 25y = 6(-3 + 3y) + -7 3 + 25y = (-3 * 6 + 3y * 6) + -7 3 + 25y = (-18 + 18y) + -7 Reorder the terms: 3 + 25y = -18 + -7 + 18y Combine like terms: -18 + -7 = -25 3 + 25y = -25 + 18y Solving 3 + 25y = -25 + 18y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-18y' to each side of the equation. 3 + 25y + -18y = -25 + 18y + -18y Combine like terms: 25y + -18y = 7y 3 + 7y = -25 + 18y + -18y Combine like terms: 18y + -18y = 0 3 + 7y = -25 + 0 3 + 7y = -25 Add '-3' to each side of the equation. 3 + -3 + 7y = -25 + -3 Combine like terms: 3 + -3 = 0 0 + 7y = -25 + -3 7y = -25 + -3 Combine like terms: -25 + -3 = -28 7y = -28 Divide each side by '7'. y = -4 Simplifying y = -4
| 4(3x+21)=24 | | 5x+1=4(x+5)+9 | | 8(x-11)-6=20x-190 | | 20+-25= | | -2(9n+4)=22-7n | | h^2-3h+c=0 | | 4m^2+2n=3 | | 6x+8-13x+10=x+6+x+3x | | -5g=g-h | | 2(3c-1)-4=4c+8 | | (3d+6)(4d-11)=0 | | 10x+3x-4= | | 12x-3x+6x+5x= | | 2x(x+5)=870 | | 5y=4y^2-6 | | 2x^2-20x-44=0 | | 6c^2-11c+3=0 | | x^5-789=0 | | 2x+3x-3+10=4x+14 | | 6x+6=-112-10x | | 12x^4+12x^3-9x^2+16x-4=0 | | 27=0.428x | | 7x+3x-4x+11=7x+17-4x | | 6x^2=2x+2 | | 6(3x+3)=-198 | | -10=0.8y+6 | | -5x+4=-3x-2 | | 6x-3+2x=-67 | | 6x-3+2x=-64 | | 4(6x+2)=-112 | | -6x+1=5x+45 | | -23=3x+x+1 |